Effervescence Accelerators: Barriers to Outsiders in Christian Interaction Rituals. (18th March 2021) - Draper, Scott
Abstract: In interaction ritual theory, barriers to outsiders are cues that communicate who is and is not excluded from a ritual. Prior research on religious rituals has established strong support for the hypothesis that barriers promote collective effervescence and social solidarity. Questions remain, though, regarding how this social dynamic impacts the practices, identities, missions, and conflicts of congregations who strive to be inclusive. We conducted microsociological analysis of rituals based on participant-observation and focus groups at six Christian congregations: Jehovah's Witnesses, Latter-day Saints, Christian Scientists, Brethren, Catholics, and Episcopalians. Barriers were built in all the rituals, bringing congregational distinction through contrast with different types of outsiders. We also observed effervescent moments where barriers were low and inconsequential, suggesting that severe barriers are unnecessary. Rather, the special ritual function of barriers is to provide instant jolts of effervescence, especially when other social dynamics are failing.